The Influence of Service Quality, Pricing, and Digital Marketing on IndiHome Fiber Costumers Loyalty - Anastasia Tobing; Ernes Simorangkir; Misdianto Situmorang; Purnama Yanti Purba (International Journal of Social Science and Business, 2021)
Customer loyalty can be influenced by several factors, including service quality, pricing, and digital marketing. This study analyzes the effect of service quality, pricing, and digital marketing on IndiHome Fiber customer loyalty. This research is a descriptive study using a quantitative approach. The population in this study amounted to 16,453 people who are consumers of IndiHome Fiber. Sampling was done by purposive sampling to obtain a sample of 99 people. Data was collected by distributing questionnaires to each sample. The data collected analyzed using multiple linear regression analysis techniques. Analysis prerequisite tests previously preceded it in normality test, multicollinearity test, and heteroscedasticity test. The results of data analysis showed that t-count (3.129) > t-table (1.98525) and -score (0.002) < (0.05), Pricing has a positive and significant score on customer loyalty. It is known that t-count (6.434) > t-table (1.98525) and -score (0.000) < (0.05), Digital Marketing has a positive and significant score on customer loyalty. It is known that t-count (3.720) > t-table (1.98525) and -score (0.000) < (0.05), as well as service quality, pricing, and digital marketing, are simultaneously significant positive on customer loyalty. It is known that F-count (93.612) > F-table (2.70) and -score (0.000) < (0.05). Based on these results, it can be concluded that, partially and simultaneously, service quality, pricing, and digital marketing have a positive and significant influence on IndiHome Fiber customer loyalty.